Shaping Resilient Futures: The Effect of PAI-Based Anti-Drug Learning Devices in Riau Province's Junior High Schools - Musa Thahir; Munzir Hitami; Zaitun Zaitun (AL-ISHLAH: Jurnal Pendidikan, 2023)
This study investigates the impact of using anti-drug learning tools based on Islamic Religious Education (PAI) in Junior High Schools in Riau Province. Through a quasi-experimental research design, two groups of students, namely the experimental group who received PAI-based anti-drug learning tools and the control group who did not receive similar treatment, were compared to measure changes in their understanding of the dangers of drugs, attitudes towards drugs, and strengthening of values. religion. Based on the results of a questionnaire distributed to 7 (seven) State Middle Schools in Riau Province, an average percentage of 74,504% was obtained in the "Good" category. These results show that PAI-based learning tools are effective in increasing students' understanding of the dangers of drugs, changing their attitudes towards drugs, and strengthening their religious values. This research provides a strong foundation for the development of similar anti-drug education programs at higher education levels and emphasizes the importance of education in efforts to prevent drug abuse among the next generation.TRANSLATE with x EnglishArabicHebrewPolishBulgarianHindiPortugueseCatalanHmong DawRomanianChinese SimplifiedHungarianRussianChinese TraditionalIndonesianSlovakCzechItalianSlovenianDanishJapaneseSpanishDutchKlingonSwedishEnglishKoreanThaiEstonianLatvianTurkishFinnishLithuanianUkrainianFrenchMalayUrduGermanMalteseVietnameseGreekNorwegianWelshHaitian CreolePersian //  TRANSLATE with COPY THE URL BELOW Back EMBED THE SNIPPET BELOW IN YOUR SITE Enable collaborative features and customize widget: Bing Webmaster PortalBack//